Štúdium avenantramidov ako významných biologicky aktívnych látok fenolového charakteru - Kulichová, Katarína; Sokol, Jozef; Maliarová, Mária (Chemické listy, 2018)
Avenanthramides are biologically active substances of phenolic nature. They are present exclusively in oats where, however, their concentrations are relatively high (200 mg kg–1). Three of avenanthramides are mostly repre-sented in the oat grains: N-[3ʹ,4ʹ-dihydroxy-(E)-cinnamoyl]--5-hydroxyanthranilic acid (2c), N-[4ʹ-hydroxy-(E)-cinna-moyl]-5-hydroxyanthranilic acid (2p) and N-[4ʹ-hydroxy- -3ʹmethoxy-(E)-cinnamoyl]-5-hydroxyanthranilic acid (2f). Avenanthramides have significant biological effects, espe-cially antioxidative, but are also interesting due to the ben-eficial effects in oncological diseases, in the process of atherosclerosis, inflammation, diabetes mellitus or derma-tological diseases. Their interesting properties may lead to the inclusion of them in potential therapeutic drugs in the future. For this reason, the need of a study of avenan-thramides as well as of the methods of their determination is increasing. In the article we provide an overview of the latest trends in the extraction and determination of avenan-thramides.
Keywords: Neoplasms; Polyphenols; arterioskleróza; polyfenoly; nádory; lidé; Antioxidants; Arteriosclerosis; Pharmacokinetics; oves; Avena; farmakokinetika; avenantramidy; antioxidancia; Humans